PROTERRA INTERNATIONAL INTER-LABORATORY PROGRAM - Neves, Célia; Borges Farias, Obede (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
At the end of 2007, the PROTERRA Iberian-American Network began an international inter-laboratory program aiming at establishing test procedures and control parameters for materials and products for earthen architecture construction. This paper reports the development and presents the results of the irst stage of this program, which aimed to deine the most appropriate procedure for determining the compressive strength of adobe. For this, two types of sampling and three different dimensions were established. The summary of the work plan, participating institutions, and details relating to the development of work in each laboratory are presented, along with the irst considerations based on the results obtained. The test results for the earth characterization, the development of the samples preparation and the procedure for implementing the compressivestrength test are highlighted. At the end, the importance of the inter-laboratory program for the establishment of procedures and for testing products’ qualiication are reviewed, highlighting those produced with earth, and the effect of the inter-laboratory program at the PROTERRA Iberian-American Network. This activity, as well as others developed within the scope of the PROTERRA Iberian-American Network, is an example of how it is possible to develop joint activities of international nature, solely with the involvement of interested professional volunteers, and disseminating knowledge gained on earthen architecture and its construction.